If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -1(x + 1) = 0 Reorder the terms: 2x + -1(1 + x) = 0 2x + (1 * -1 + x * -1) = 0 2x + (-1 + -1x) = 0 Reorder the terms: -1 + 2x + -1x = 0 Combine like terms: 2x + -1x = 1x -1 + 1x = 0 Solving -1 + 1x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 1x = 0 + 1 Combine like terms: -1 + 1 = 0 0 + 1x = 0 + 1 1x = 0 + 1 Combine like terms: 0 + 1 = 1 1x = 1 Divide each side by '1'. x = 1 Simplifying x = 1
| (8y-5)6y-7= | | 4(x+5)5=2x-4 | | 6d-11/2=2d-13/2 | | (X+10)2=y+100 | | 24x+19x=180 | | 7/10x=14/5 | | 17-x=172 | | 70-61x+4x^2=0 | | -3=-6-x | | -24+5x+x^2=0 | | x^3+3x^2-15x=0 | | -24+x^2=0 | | -9(x+9)+4=-77 | | 18000=p(1+.12*2) | | 21y=4(5x-6) | | 7(4s+1)=63 | | 70-16x+4x^2=0 | | 2b=20-28 | | 5c+15=15+4c-2 | | 5+x-4=14 | | 7x+4-2x=5x+4 | | (e^5x+3)-8=0 | | n-45+25-9= | | 2x+6x=-5+7 | | y=.0388ln(x)+.0366 | | 4(x-3)=2x-7 | | (9h-7j+8k)-9(-9h+2j-2k)= | | 5x+4y+7x-4y= | | 7x-5=3x+5+4x | | 2-x=5-3x | | -5+7=6x+2x | | f(X)=2X+6X-3 |